Extracellular fluid volume expansion, arterial stiffness and uncontrolled hypertension in patients with chronic kidney disease. Issue 8 (25th February 2019) - Braam, Branko; Lai, Chung Foon; Abinader, Joseph; Bello, Aminu K
Abstract: Background: Hypertension is prevalent in patients with chronic kidney disease (CKD) and is related to extracellular fluid volume (ECFV) expansion. Arterial stiffening is another implication of CKD that can be caused by ECFV expansion. In this study, we hypothesized that CKD patients with uncontrolled hypertension are more likely to be fluid volume expanded than normotensive patients, which in turn is associated with increased arterial stiffness. Methods: Adult hypertensive patients with mild–severe CKD ( n  = 82) were recruited. ECFV was assessed using multifrequency bioimpedance and arterial stiffness by applanation tonometry and oscillometry. Results: Patients with uncontrolled hypertension had fluid volume expansion compared with controls (1.0 ± 1.5 versus 0.0 ± 1.6 L, P < 0.001), and had a higher augmentation index (AIx) and pulse wave velocity. Fluid volume expansion was more prevalent in patients with uncontrolled hypertension (58%) than patients who were at target (27%). Fluid volume expansion was correlated with age, AIx and systolic blood pressure. In a binary logistic regression analysis, AIx, age and fluid volume status were independent predictors of uncontrolled hypertension in both univariate and multivariate models. Discussion: In summary, uncontrolled hypertension among hypertensive CKD patients is associated with ECFV expansion. Our data suggest a relationship between ECFV expansion, increased arterial stiffness and uncontrolled hypertension.